Métodos de trabajo en el quehacer del profesional de enfermería: reflexiones acerca del proceso (1999)
ABSTRACT: The theoretical framework for the need a work method for any profession and the various professional performance profiles is explained. In the case of nursing, focuses on the nursing process is done as a tool for healthcare and ideas shared by patients to the nursing staff and the profession as a social discipline. Finally the article draws a reflection on the commitment the nursing staff and teaching and health institutions must undertake on having a work method in nursing everyday activities.